2001
DOI: 10.1063/1.1371002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effective electrostriction coefficients in ferroelectric thin films

Abstract: Electromechanical properties of a number of ferroelectric films including PbZrxTi1−xO3(PZT), 0.9PbMg1/3Nb2/3O3–0.1PbTiO3(PMN-PT), and SrBi2Ta2O9(SBT) are investigated using laser interferometry combined with conventional dielectric measurements. Effective electrostriction coefficients of the films, Qeff, are determined using a linearized electrostriction equation that couples longitudinal piezoelectric coefficient, d33, with the polarization and dielectric constant. It is shown that, in PZT films, electrostric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 28 publications
2
65
0
Order By: Relevance
“…In reality lattice imperfections or defects can pin domain walls, hinder their movement, and reduce the extrinsic contribution. 20,21 The extrinsic contribution to electrocaloric response will be zero in the case of completely pinned domain walls, and our calculation, in effect, places an upper bound on the extrinsic contribution to the electrocaloric properties. Recent experimental results have demonstrated that while it is challenging to fabricate defect-free ferroelectric films, advances in thin film growth techniques can yield low defect density films, a few hundred nanometers in thickness, that exhibit significant extrinsic contributions to the dielectric response.…”
Section: à ámentioning
confidence: 99%
“…In reality lattice imperfections or defects can pin domain walls, hinder their movement, and reduce the extrinsic contribution. 20,21 The extrinsic contribution to electrocaloric response will be zero in the case of completely pinned domain walls, and our calculation, in effect, places an upper bound on the extrinsic contribution to the electrocaloric properties. Recent experimental results have demonstrated that while it is challenging to fabricate defect-free ferroelectric films, advances in thin film growth techniques can yield low defect density films, a few hundred nanometers in thickness, that exhibit significant extrinsic contributions to the dielectric response.…”
Section: à ámentioning
confidence: 99%
“…Well-known examples are lead magnesium niobate ͑PMN͒, lead zinc niobate ͑PZN͒, and their solid solutions with lead titanate ͑PT͒, which are the most widely studied relaxor materials. [8][9][10][11] However, some lead-free compounds were also recently found to present a relaxor behavior. In BaZr x Ti 1Ϫx O 3 compounds, the relaxor behavior depends on the zirconium content.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)), i.e., different from the parameter b reported for thymine powder 38 (27.862 Å ). We hypothesize that significant structural distortions due to the presence of water in the crystal lattice might be an indication of the potential polar behavior [39][40][41] as will be experimentally delineated below.…”
Section: Resultsmentioning
confidence: 99%